Understanding the treatment of acute pancreatitis and its complications -a database for assessing traditional Chinese medicine use - Zhou, Xin; Yang, Yu; Liu, Ya-Li; Hao, Wei-An; Ao, Xin-Yi; Liu, Jian-Qin; Zhang, Yang; Li, Zhi (Frontiers in Pharmacology, 2025)
IntroductionIntegrative medicine combining traditional Chinese medicine (TCM) with biomedicine has become a notable approach for treating acute pancreatitis (AP). However, the absence of a comprehensive and reliable database to store and organize TCM-related data for the prevention and treatment of AP presents a significant challenge for the development of herbal medicines. To develop a comprehensive, user-friendly platform for browsing, querying, and analyzing TCM-related data for treating AP.MethodsTCM-related data for treating AP were systematically extracted from the literature and established databases. The front-end interface was developed using HyperText Markup Language, Cascading Style Sheets, and JavaScript to enhance user experience. The back-end employed Hypertext Preprocessor and My Structured Query Language for improved performance and security. The Smarty template engine was utilized to separate the front-end and back-end, facilitating efficient updates to the TCMAP platform.Results and discussionThe current version of the TCMAP includes: (i) documentation of 200 evidence-based TCM formulations, with comprehensive details on clinical applications, targets related to AP, and target pathway enrichment analysis, including 449 herbs; (ii) records of 58 natural metabolites, involving extensive information on their potential targets and pharmacological properties; and (iii) integration with a web server enables users to conduct similarity and enrichment analyses of input prescriptions based on herbs, metabolites, and genes. Furthermore, TCMAP also supports discovering anti-AP herb pairs with similar metabolites and targets. Network analysis further provides users with the intrinsic properties of anti-AP formulations. The TCMAP provides a robust data platform for predicting new metabolites and exploring the potential mechanisms of TCM in treating AP. The TCMAP is accessible at https://cellknowledge.com.cn/tcmap.